The Sensibility of Cyber Community in The Multicultural Space: Reading the Practice of Digital Ethnography in Kampoeng Cyber Jogja - Aprinus Salam; Rina Zuliana (Journal of International Conference Proceedings (JICP), 2021)
This study aims to reveal the sensibility and the sociocultural practice of the KCJ cyber community in a multicultural space. This research uses digital ethnographic methods to reveal the cultural practices of cyber societies and cultural productions born from their new habits. Indirectly, the impact of alleviating society from the digital divide led them to sociocultural change. The KCJ community entered into a hybrid space. The online activities of the KCJ community form a local-multimedia sensibility, both of a general nature such as limited internet access by looking at the world globally or explicitly using the Internet as a medium of interaction and communication with only a limited community. In practice, KCJ's sensibility as a multimedia society mingles with the traditional sensibility that social practices still follow local customs, values, and norms.